Suppression of vision by transcranial magnetic stimulation: a third mechanism. - Corthout, E; Uttl, B; Juan, C; Hallett, M; Cowey, A (2000)
We recently reported three periods when single-pulse transcranial magnetic stimulation (TMS) of the occipital pole impaired performance on a forced-choice visual letter-identification task. TMS-induced suppression during these periods is best explained by a blink-associated covering of the pupils and by a direct interference with letter-processing neural activity. We now report TMS-induced suppression at times that seem too late for the suppression to be explained by the first mechanism and too early for the suppression to be explained by the second mechanism. The most likely explanation is a blink-associated interference with letter-processing neural activity.